Investigation of gamma-ray shielding parameters of bismuth phospho-tellurite glasses doped with varying Sm2O3. Issue 11 (November 2022) - Kolavekar, S.B.; Hiremath, G.B.; Patil, Prashant N.; Badiger, N.M.; Ayachit, N.H.
Abstract: The gamma ray shielding parameters such as mass attenuation coefficient, effective atomic number, equivalent atomic number, exposure buildup factor, and energy absorption buildup factor were determined for the 47.5P2 O5 +45ZnO+(5-x) Bi2 O3 +2.5TeO2 +xSm2 O3 glass system using Phy-X/PSD software in the energy range from 0.015 to 15 MeV at penetration depths of 1–40 MFP. To understand the effect of Sm2 O3 on gamma ray shielding parameters in selected glass system, the Sm2 O3 was varied in the glass from 0.01 to 1 mol%. The calculated results show that the mass attenuation coefficient decreases with increasing photon energy but not influenced by the addition of Sm2 O3 . The Zeq values are lower in low (≤100 keV) and high energy regions (1 MeV–15 MeV) and higher in the medium energy region, indicating that the Compton scattering is significant in the medium energy region. The values of exposure buildup factors and energy absorption buildup factors are smaller in the low and high energy regions than in the intermediate energy region, indicating that the photo absorption and pair creation processes are important in the low and high energy regions, respectively. The 1% mole concentration of Sm2 O3 in the selected glass shows higher exposure buildup factor and energy absorption buildup factor values in the intermediate energy region. The high density, high effective atomic number, and transparency to visible light of these materials indicate that they can be used as shielding materials in nuclear reactors and nuclear technology. Abstract : Glass; Shielding; Attenuation; Sm2 O3 ; Effective atomic number; Buildup factor.